2015
DOI: 10.1002/adma.201500846
|View full text |Cite
|
Sign up to set email alerts
|

Rotation‐Misfit‐Free Heteroepitaxial Stacking and Stitching Growth of Hexagonal Transition‐Metal Dichalcogenide Monolayers by Nucleation Kinetics Controls

Abstract: 2D vertical stacking and lateral stitching growth of monolayer (ML) hexagonal transition-metal dichalcogenides are reported. The 2D heteroepitaxial manipulation of MoS2 and WS2 MLs is achieved by control of the 2D nucleation kinetics during the sequential vapor-phase growth. It enables the creation of hexagon-on-hexagon unit-cell stacking and hexagon-by-hexagon stitching without interlayer rotation misfits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
125
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(129 citation statements)
references
References 46 publications
(48 reference statements)
4
125
0
Order By: Relevance
“…The variation of size and thickness of WS 2 flakes in the previous discussion can be easily understand by the adsorption/desorption and the dynamics of surface diffusion of precursor species on the substrate [37]. If the growth temperature is too low, then S-precursors and WO 3 -precursors have a low surface diffusion rate and the adsorption energy is not sufficient [38,39].…”
Section: Resultsmentioning
confidence: 99%
“…The variation of size and thickness of WS 2 flakes in the previous discussion can be easily understand by the adsorption/desorption and the dynamics of surface diffusion of precursor species on the substrate [37]. If the growth temperature is too low, then S-precursors and WO 3 -precursors have a low surface diffusion rate and the adsorption energy is not sufficient [38,39].…”
Section: Resultsmentioning
confidence: 99%
“…Due to the special crystal structure, it is extremely challenging to construct TMDbased epitaxial heterostructure with edge contact (i.e., lateral heterostructures) since very few materials have lattice parameters matching the edges of TMDs [24,[108][109][110][111]. So far, most of the reported lateral heterostructures are limited to two TMD components, such as MoS 2 -MoSe 2 and MoS 2 -WS 2 [112][113][114][115][116]. Recently, our group reported a new type of lateral heterostructure consisting of layered TMD material and another non-layered nanomaterial [117].…”
Section: D Nanostructures Grown On 1d Seedsmentioning
confidence: 99%
“…Figure S14(a) shows the dark field scanning transmission electron microscopy (DF-STEM) image of the domain, in which the inner darker MoS 2 and the outer brighter WS 2 exhibit obvious contrast. Meanwhile, the selected area electron diffraction (SAED) patterns collected from MoS 2 , WS 2 (shown in SI 14) and the stitching interface (the inset of figure 4(e)) share the same hexagonal unitcell orientations, demonstrating the high crystalline quality with free-misfit rotation [16]. HRTEM images for both sides of MoS 2 -WS 2 heterostructure show the periodic atom arrangements as shown in figures 4(f), (g), which is corresponding to figure 1.…”
Section: Growth Of Mos 2 -Ws 2 Heterostructuresmentioning
confidence: 99%
“…For the two-step method, the inside core is grown first and the outside edge is grown afterwards [14][15][16][17][18]. Li et al reported the growth of a WSe 2 -MoS 2 p-n junction by sequent growth of WSe 2 and MoS 2 using low pressure CVD [7].…”
Section: Introductionmentioning
confidence: 99%